Implementasi Manajemen Strategi dalam Meningkatkan Efisiensi Pendidikan Islam - Julia Rosalinda; Ahmad Subagyo; Muhammad Sofyan Hadi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Strategic management plays a crucial role in improving the efficiency of Islamic education amid various challenges, such as limited resources, low management efficiency, and suboptimal learning strategies. This study aims to analyze the implementation of strategic management in enhancing the efficiency of Islamic education. Using a qualitative descriptive research method, this study examines the applied strategies, supporting and inhibiting factors, and the impact of strategy implementation on the efficiency of Islamic educational institutions. The findings indicate that effective strategic management implementation can enhance learning quality, optimize budget utilization, and strengthen the competitiveness of Islamic educational institutions. The adoption of digital administration systems, improvement of educators' competencies, diversification of funding sources, and collaboration with various stakeholders are required to achieve optimal efficiency.